Pengaruh Fleksibilitas dan Perilaku Inovasi Terhadap Retensi Karyawan PT Jaya Jagat Raya Sidoarjo - Laila Torfiah; Naila Nurul Faizah; Misbachul Munir (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The rapid progress in information and communication technology coincides with globalization in the field of human resource management and will determine the status of human resource management in companies now and in the future. The author uses a quantitative research method through a random sampling approach and data collection process through distributing questionnaires. The research sample used 30 staff who were taken randomly from 45 marketing staff. The results of this study indicate that flexibility and innovation behavior factors have an effect on employee retention at PT Jaya Jagat Raya.